Evaluation of Nicotine and the Components of e-Liquids Generated from e-Cigarette Aerosols. Issue 8 (26th October 2018) - Peace, Michelle R; Mulder, Haley A; Baird, Tyson R; Butler, Karen E; Friedrich, Alaina K; Stone, Joseph W; Turner, Joseph B McGee; Poklis, Alphonse; Poklis, Justin L
Abstract: Electronic cigarettes (e-cigs) deliver nicotine in an aerosol to the user that simulates the smoke of traditional cigarettes purportedly without the pathology of inhaling tobacco smoke due to the absence of combustion. Advanced versions of e-cigs enable the user to potentially moderate the concentration of drug in the aerosol by selecting from a range of voltages on the power supply. A method was developed to trap the aerosol produced by a KangerTech AeroTank, 1.8 Ω preassembled atomizer in order to analyze the concentration of nicotine and to evaluate the constituents of the aerosol at various voltages on the power supply. A 12-mg/mL formulation of nicotine in 50:50 propylene glycol (PG):vegetable glycerin (VG) was used to produce aerosol at 3.9, 4.3 and 4.7 V. The aerosol was trapped in a simple glass assemblage and analyzed by a 3200 Q Trap HPLC–MS-MS. The dose of nicotine delivered in the aerosol at 3.9, 4.3 and 4.7 V was determined to be 88 ± 12 μg, 91 ± 15 μg and 125 ± 22 μg. The average recovery of nicotine in the trap across the voltages was 99.8%. The glass trap system was an effective device for collecting the aerosol for analysis and an increase in drug yield was observed with increasing voltage from the power supply on the e-cig. The glass trap system was also used in combination with a 100-μm solid-phase microextraction fiber to capture the aerosol and analyze it via DART–MS and GC–MS. Four commercial e-liquids labeled to contain nicotine were aerosolized at 4.3 V. The pharmacologically active ingredient, nicotine, as well as PG, VG and a number of flavoring agents found in these formulations were identified.